SCIENCE DIPLOMACY: FRENCH EXPERIENCE - A. V. Shestopal; N. V. Litvak (Vestnik MGIMO-Universiteta)
The article deals with the formulation in France in the early twenty-first century of a new kind of diplomacy - science diplomacy. It studies the reasons for this process and its problems. On the one hand, the French foreign policy doctrine presupposes an ability to exercise certain influence on its international partners. However, its goals in this area are reduced to mere survival under conditions dictated by other countries. Modern trends in the world of science, which lead to integration, force to reconsider the attitude towards staff training, to research itself, and to its place and role in politics and diplomacy. However, an achievement of the French political class is an understanding of the main aspects of what is happening. This understanding leads to the search for ways to adapt to the new situation. At the same time, diplomats can operate only with those resources that are available to them. Competition with the US, China and other countries for scientific personnel and achievements cannot be won by diplomatic means alone, without backing by appropriate legal, economic and other efforts which provide favorable conditions for winning the competition. The main causes of France's unfavorable position in the struggle for an independent science are economic and political. It is they that lead to conditions, which prohibit French scientists to live up to their potential at home.